(untitled) (Bangladesh Heart Journal, 2016)
Sarcoidosis is a well known systemic disorder that invariably involves lungs. However, pulmonary hypertension and cor-pulmanle are not common due to pulmonary involvement of sarcoidosis. We report a case of pulmonary hypertension leading to corpulmonale due to sarcoidosis. An elderly female suffering from hypertension & sarcoidosis developed complications and arrived at the diagnosis by correlating various investigations. X-ray chest (P/A) showed cardiomegaly (right ventricular type), reticulo-nodular shadow involving both mid and lower zone; characteristic high resolution CT (HRCT) scan appearances include reticulonodular opacities; pulmonary function test showed restrictive type of defect; ECG showed right ventricular hypertrophy with strain pattern; in echocardiogram there were right ventricular hypertrophy (RVH) with pulmonary artery systolic pressure (PASP) of 63 mmHg indicating severe pulmonary arterial hypertension (PH); along with significantly elevated B-type natriuretic peptide(BNP) level. Bangladesh Heart Journal 2015; 30(1) : 37-42